10 pennies, 16 dimes, 19 nickles.
Sorry I'm not from US so I don't know your currency. Sorry about that. Hope what I have given you is enough. :)
Looks like the given limit is
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D)
With some simple algebra, we can rewrite
![\dfrac n{3n-1} = \dfrac13 \cdot \dfrac n{n-9} = \dfrac13 \cdot \dfrac{(n-9)+9}{n-9} = \dfrac13 \cdot \left(1 + \dfrac9{n-9}\right)](https://tex.z-dn.net/?f=%5Cdfrac%20n%7B3n-1%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cdfrac%20n%7Bn-9%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cdfrac%7B%28n-9%29%2B9%7D%7Bn-9%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cleft%281%20%2B%20%5Cdfrac9%7Bn-9%7D%5Cright%29)
then distribute the limit over the product,
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1} = \lim_{n\to\infty}\left(\dfrac13\right)^{n-1} \cdot \lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%28%5Cdfrac13%5Cright%29%5E%7Bn-1%7D%20%5Ccdot%20%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D)
The first limit is 0, since 1/3ⁿ is a positive, decreasing sequence. But before claiming the overall limit is also 0, we need to show that the second limit is also finite.
For the second limit, recall the definition of the constant, <em>e</em> :
![\displaystyle e = \lim_{n\to\infty} \left(1+\frac1n\right)^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20e%20%3D%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%281%2B%5Cfrac1n%5Cright%29%5En)
To make our limit resemble this one more closely, make a substitution; replace 9/(<em>n</em> - 9) with 1/<em>m</em>, so that
![\dfrac{9}{n-9} = \dfrac1m \implies 9m = n-9 \implies 9m+8 = n-1](https://tex.z-dn.net/?f=%5Cdfrac%7B9%7D%7Bn-9%7D%20%3D%20%5Cdfrac1m%20%5Cimplies%209m%20%3D%20n-9%20%5Cimplies%209m%2B8%20%3D%20n-1)
From the relation 9<em>m</em> = <em>n</em> - 9, we see that <em>m</em> also approaches infinity as <em>n</em> approaches infinity. So, the second limit is rewritten as
![\displaystyle\lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1} = \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m+8}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%2B8%7D)
Now we apply some more properties of multiplication and limits:
![\displaystyle \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m+8} = \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m} \cdot \lim_{m\to\infty}\left(1+\dfrac1m\right)^8 \\\\ = \lim_{m\to\infty}\left(\left(1+\dfrac1m\right)^m\right)^9 \cdot \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)\right)^8 \\\\ = \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)^m\right)^9 \cdot \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)\right)^8 \\\\ = e^9 \cdot 1^8 = e^9](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%2B8%7D%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%7D%20%5Ccdot%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%28%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Em%5Cright%29%5E9%20%5Ccdot%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Em%5Cright%29%5E9%20%5Ccdot%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20e%5E9%20%5Ccdot%201%5E8%20%3D%20e%5E9)
So, the overall limit is indeed 0:
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1} = \underbrace{\lim_{n\to\infty}\left(\dfrac13\right)^{n-1}}_0 \cdot \underbrace{\lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1}}_{e^9} = \boxed{0}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Cunderbrace%7B%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%28%5Cdfrac13%5Cright%29%5E%7Bn-1%7D%7D_0%20%5Ccdot%20%5Cunderbrace%7B%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D%7D_%7Be%5E9%7D%20%3D%20%5Cboxed%7B0%7D)
Answer:
Step-by-step explanation:
The expression representing the amount of money that the photographer would make from selling 10 copies is given as
10(0.75p - 0.5)
where p represents the price determined for each copy. Assuming the price charged per copy is $5, then the amount made from 10 copies is
10(0.75 × 5 - 0.5) = $32.5
It could have been
10(5 - 0.5) = $45
The price is being reduced by 25%(100 - 75)
Therefore, the option that most likely describes the agreement between the online service company and the photographer is
A. The company keeps 25% of the amount paid for each copy and charges the photographer $0.50 for every copy purchased.
Y=mx+b
so is 2
the last number of the equation
Answer:
hahaha I stole your points lololoooooooooooollllllllllolololol
Step-by-step explanation:
JK, if you are asking how many hours it would take to make 242 dolla then the answer is 11